2018
DOI: 10.1097/md.0000000000012508
|View full text |Cite
|
Sign up to set email alerts
|

Oral health status of adult heart transplant recipients in China

Abstract: Limited information on the oral health status of adult heart transplant recipients (HTRs) is known, and no available data exist in China. A prerequisite dental evaluation is usually recommended for patients’ postorgan transplantation because lifelong immunosuppression may predispose them to infection spread.The aim of this study was to investigate the oral health status of Chinese adult HTRs and determine the association between oral health status and history of heart transplantation (HT).We carried out a cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 23 publications
2
9
0
2
Order By: Relevance
“…Accordingly, a high periodontal treatment need of patients with HI and after HTx, which is almost higher than for the German general population in the DMS V [20] can be concluded. This result is in line with a recent Chinese cross-sectional study, which presented worse periodontal conditions for HTx recipients, while dental care status was comparable to healthy controls [12]. Similarly, patients who received a solid organ transplantation (kidney, liver, lung) were found to present high periodontal treatment need, irrespective of time since transplantation [7,8,9,10,11].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Accordingly, a high periodontal treatment need of patients with HI and after HTx, which is almost higher than for the German general population in the DMS V [20] can be concluded. This result is in line with a recent Chinese cross-sectional study, which presented worse periodontal conditions for HTx recipients, while dental care status was comparable to healthy controls [12]. Similarly, patients who received a solid organ transplantation (kidney, liver, lung) were found to present high periodontal treatment need, irrespective of time since transplantation [7,8,9,10,11].…”
Section: Discussionsupporting
confidence: 87%
“…Data for heart transplant recipients are still rare in the literature. A recent Chinese cross-sectional study presented worse periodontal conditions for heart transplant recipients [12]. It was also shown that periodontal inflammation would be associated with systemic inflammatory parameters in heart transplanted individuals [13].…”
Section: Introductionmentioning
confidence: 99%
“…A previous cross-sectional study of patients with HF and after HTx also showed a high periodontal treatment need of these patients [18]. Moreover, another recent cross-sectional study of Chinese HTx recipients also found high periodontal treatment need for these patients [12]. Furthermore, patients with other solid organ transplantation, including kidney, liver and lung suffer from a high periodontal treatment need, regardless of their time period since transplantation [13].…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, patients with heart transplantation were found to suffer from high periodontal treatment need [12]. While further data for heart transplant recipients are lacking, findings of patients with other solid organ transplantations suggest the absent of sufficient rehabilitation before and maintenance after transplantation [13].…”
Section: Introductionmentioning
confidence: 98%
“…(3)(4)(5)(6) Cardiovascular diseases, respiratory diseases, diabetes, and adverse outcomes of pregnancy are associated with oral diseases including periodontitis. (2,7,8) Bacterial endocarditis is one of the most serious problems in dentistry. (9) The incidence of systemic diseases in studies conducted in India, Saudi Arabia, Tehran, and Mashhad has been reported to be 10.3% to 52.8%.…”
Section: Introductionmentioning
confidence: 99%